Archaeology of settlement and migratory patterns of the Fur tribe in Darfur, Sudan - Gutierrez, Shaheen (My University, 2008)
The state of Darfur is located around the Jebel Marra Mountains in western Sudan, Africa, and was first established around A.D. 1630 by the ruling African tribe known as the Fur. The Fur tribe homeland is divided amongst three Fur divisions, speaking six traditional dialects, and is located in the center and western border of Darfur. These dialects and traditions are quickly being erased by the assimilation Darfurians face by being forced to migrate across Sudan, often into eastern Chad, leaving behind their native culture. The detriment of militia groups in Darfur, Sudan upon the personal Sudanese identity can be examined in the archaeological record by comparing the transitional settlement patterns and purpose of the Meidob Hills and Tila Island against those of the modern villages Mukjar, Dor, Shoba, and the Turra Burial Grounds. Understanding the shift of traditional living and settlement patterns of the Fur tribe is beneficial to archaeologists, because it will be reflected in the archaeological record as a precursor signature of cultural genocide.
Keywords: Demographic archaeology -- Sudan -- Darfur; Land settlement patterns -- Sudan -- Darfur; Fur (African people) -- Sudan -- Darfur -- Migrations